Microplastics distribution on the beach sediment based on satellite remote sensing: a case study in Bali, Indonesia - Abdull Manap, Mohd Rashidi; Imizan, Muhammad Ibadurrahman; Dams, Jannik Werner; Sepulveda, Felipe D.; Muratore, Anna; Notargiacomo, Lorenza; Ferrara, Fulvio; Mukhni, Nur Hayatna (Elsevier B.V., 2026)
Microplastic (MP) pollution is increasingly recognized as a critical issue in coastal environments, where complex interactions between ocean currents, winds, waves, and human activities govern the transport and deposition of synthetic particles. Although previous studies in Asia have documented MPs accumulation linked to riverine discharge, tourism pressures, and monsoonal circulation, limited work has integrated polymer-level characterization with site-specific hydrodynamic drivers, particularly along the coastlines of Bali. This study addresses this gap by examining how seasonal oceanographic processes influence MPs composition and distribution across three beaches: Keramas Beach (KB), Nyang Nyang Beach (NNB), and Balangan Beach (BB), between January and July 2024. This study provides a baseline, site-specific assessment of microplastic occurrence, polymer composition, and size distribution in three selected beach sediments of Bali, intended to establish reference conditions. Seventeen beach sediments were sampled and processed through dry sieving, microscopy, and attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy to identify particle sizes, morphologies, and polymer types. Hydrodynamic conditions were reconstructed using satellite-derived datasets from the Copernicus Marine Environment Monitoring Service (CMEMS) and the Copernicus Atmosphere Monitoring Service (CAMS), alongside estimates of riverine plastic discharge. A total of 10 MP particles (<5 mm) were identified, with polystyrene (PS) as the dominant polymer, followed by polypropylene (PP), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), and three copolymers. MPs occurred primarily as fragments within the 2.5–5 mm range. The average MP concentrations were 2.54 ± 2.30, 2.04 ± 2.49, and 0.61 ± 1.37 MPs/kg dry weight (dw) at KB, NNB, and BB, respectively, following the order KB > NNB > BB. Spatial variability corresponded closely with hydrodynamic patterns: KB exhibited the highest MP concentration due to onshore winds and southwestward currents from the Lombok Strait; BB showed low retention driven by offshore wind stress and weak currents; and NNB displayed intermediate accumulation influenced by longshore drift and moderate river inputs. These findings highlight the value of integrating spectroscopic analysis with remote-sensing hydrodynamics to explain mechanisms of MP deposition, offering a strengthened basis for targeted monitoring, predictive modeling, and coastal pollution management in Bali and neighboring islands.